OPTIMIZATION OF THE WHEY SEPARATION PROCESS (Sciences & Technology. A, exactes sciences, 2003)
The separation process of  the whey resulting from milk coagulation in cheese manufacturing was modelized and optimized for different coagulae. Preliminary investigations of the filtration process allowed to choose the kind of coagulum and the ranges of the key-parameters. The pressing process was further modelized and optimized using a 32 experiment design. The effects of time (t) of coagulum pressing and the pressing force were investigated in the respective range: 0-6 hours and 0,005-0,009 kg/cm2. It was found that the optimum process is strongly correlated to the kind of coagulum. For instance, for coagulum obtained using promoter agents, this optimum occurs at a pressing time of 4,9 hours and a pressing force of 0,0064 kg/cm2. For tainted milk, this optimum lies at top : 7,2 hours and 0,008 kg/cm2. The results highlight the opportunity to achieve a high performance whey recovery using a low-cost process.